Using prosocial behavior to safeguard mental health and foster emotional well-being during the COVID-19 pandemic: A registered report of a randomized trial. - Andrew Miles; Meena Andiappan; Laura Upenieks; Christos Orfanidis (PLoS ONE, 2022)
Background The COVID-19 pandemic, the accompanying lockdown measures, and their possible long-term effects have made mental health a pressing public health concern. Acts that focus on benefiting others-known as prosocial behaviors-offer one promising intervention that is both flexible and low cost. However, neither the range of emotional states prosocial acts impact nor the size of those effects is currently clear-both of which directly influence its attractiveness as a treatment option. Objective To assess the effect of prosocial activity on emotional well-being (happiness, belief that one's life is valuable) and mental health (anxiety, depression). Methods 1,234 respondents from the United States and Canada were recruited from Amazon's Mechanical Turk and randomly assigned (by computer software) to perform prosocial (N = 411), self-focused (N = 423), or neutral (N = 400) behaviors three times a week for three weeks. A follow-up assessment was given two weeks after the intervention. Participants were blind to alternative conditions. Analyses were based on 1052 participants (Nprosocial = 347, Nself = 365, Nneutral = 340). Findings Those in the prosocial condition did not differ on any outcome from those in the self-focused or neutral acts conditions during the intervention or at follow-up, nor did prosocial effects differ for those who had been negatively affected socially or economically by the pandemic (all p's > 0.05). Exploratory analyses that more tightly controlled for study compliance found that prosocial acts reduced anxiety relative to neutral acts control (β = -0.12 [95% CI: -0.22 to -0.02]) and increased the belief that one's life is valuable (β = 0.11 [95% CI: 0.03 to 0.19]). These effects persisted throughout the intervention and at follow-up. Conclusion Prosocial acts may provide small, lasting benefits to emotional well-being and mental health. Future work should replicate these results using tighter, pre-registered controls on study compliance.